Diagnostic Errors in Aesthetic Gynecology: A Review of Recent Evidence (2020-2025) - Gadoyeva Dilshoda Abdigaffor kizi (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Abstract. Background: Aesthetic gynecology, encompassing elective procedures to enhance the appearance and function of the female genital tract, has grown in demand. With increasing complexity and elective nature of these interventions, the risk of diagnostic errors—misdiagnosis, delayed diagnosis, incorrect patient selection or misunderstanding of underlying pathology—becomes relevant. Objective: This review aims to summarise the evidence from 2020-2025 on diagnostic errors in aesthetic gynecology, identify contributory factors, and suggest strategies to minimise harm.